The Microbiome Connection: A Common Pathway Linking Cancer and Heart Failure - Ioannis Paraskevaidis; Elias Tsougos; Christos Kourek (Biomedicines, 2025)
In humans, heart failure (HF) and cancer are among the leading causes of morbidity and mortality. A growing body of evidence highlights a bidirectional relationship between these conditions, underpinned by shared risk factors and overlapping pathophysiological pathways. This review aims to explore the emerging role of the intestinal microbiome as a common mechanistic link between HF and cancer. Specifically, we examine how microbial dysbiosis and its metabolic products—such as trimethylamine N-oxide (TMAO), short-chain fatty acids (SCFAs), bile acids, lipopolysaccharides (LPS), and branched-chain amino acids (BCAAs)—contribute to inflammation, immune dysregulation, oxidative stress, and metabolic dysfunction. These mechanisms promote multiorgan impairment and establish a vicious cycle that fuels both tumorigenesis and cardiac deterioration. HF, cancer, and the gut microbiome are not isolated entities but are deeply interconnected through shared biological mechanisms—including chronic inflammation, microbial dysbiosis, immune and neurohumoral modulation, and metabolic derangement. These findings support the concept of a microbiome-centered axis involving the gut, heart, and tumors, which may underlie many chronic disease processes. Understanding these interactions may provide novel insights into disease pathogenesis and uncover promising therapeutic targets that leverage microbiome modulation to prevent or treat HF, cancer, and other systemic diseases.